Politik Belanja Daerah Hadapi Fase Awal Pandemi: Studi Kasus 34 Provinsi di Indonesia - Ramda, Eduardo (Ministry of Home Affairs, 2023)
Several regulations issued as guidelines for implementing budget reallocation and program refocusing in the Early Phase of the Pandemic needed to be revised. This study aims to observe the practice of regional expenditure realization during the initial phase of the 2020 pandemic in Indonesia. This study uses a qualitative method by combining literature and spatial analysis. The determinant factor that supports the successful implementation of budget reallocation, program refocusing, and realization of regional expenditures is the application of administrative sanctions to regional governments that do not work according to the target. The sluggish performance of regional governments is caused by bureaucratic obstacles, limited knowledge of regulations, and fears of imposition of sanctions if they make wrong decisions. Data shows that out of 34 provinces, only four can carry out budget realization and spend over 80% on handling the impact of COVID-19. In the end, regional spending politics in Indonesia is focused on two keywords, namely pressure and political will to change.